The use of digital tools for the disclosure of sustainability reports in the tourism sector - Paiva, I. S.; Carvalho, L. C. (Handbook of Research on Entrepreneurship and Marketing for Global Reach in the Digital Economy, 2019)
Sustainability is a key topic in tourism because this activity uses territory and local resources intensively. Sustainability is considered as a triple bottom line with the three vertices: environmental, social, and economic. Tourism nowadays is an economic and social phenomenon. Even in a period of crisis, tourism has experienced continued growth and widening diversification to become one of the most important sectors in the worldwide economy. Tourism uses more and more digital tools to communicate with stakeholders. This chapter has a twofold purpose: 1) to analyze the disclosure of information provided to stakeholders using digital tools; 2) to compare the sustainability reports provided by a company with the corporate sustainability report guidelines. This chapter uses a qualitative methodology to study the case of the Pestana Group. The Pestana Group is currently the largest Portuguese hospitality group with operations and hotels all over the world, and this case may provide some clues about the use of digital tools to communicate sustainability results to stakeholders.